Five‐year mortality of severely malnourished patients with chronic anorexia nervosa admitted to a medical unit - M. Guinhut; Nathalie Godart; Mohamed Amine Benadjaoud; Jean‐Claude Melchior; Mouna Hanachi (2020)
Abstract Objective Anorexia nervosa (AN) is associated with one of the highest mortality rates of any psychiatric disorder but limited mortality data were reported for those with extremely severe malnutrition. This study aimed to estimate standardized mortality ratio (SMR), investigate predictive factors of mortality and causes of death among a sample of patients with AN admitted to a specialized clinical nutrition unit (CNU) because of extremely severe malnutrition. Methods Between 11/27/1997 and 01/15/2014, vital status was determined for 384 patients admitted for AN at the first time in the CNU. Sociodemographic, anamnestic, and clinical data were collected. We calculated the SMR. Univariate and multivariate Cox regression analyses were performed to identify mortality predictors. Results Crude mortality rate was 11.5%. (44 deaths) and SMR 15.9 [CI 95% (11.6–21.4)], 5.2 years post inpatient treatment. Mortality predictors at the time of hospitalization were as follows: older age, occurrence of an in‐hospital suicide attempt, transfer to medical intensive care unit and the following somatic complications: frank anemia, dysnatremia, infectious and cardiac complications. Other predictors of mortality were: past or present history of discharge against medical advice, hematological comorbidities (not related to AN). A longer inpatient length of stay was a protective factor. Conclusion Very severely malnourished patients with AN hospitalized in a medical unit because of extremely severe somatic issues have a medium‐term mortality rate higher than the general population and even higher than patients in tertiary specialized ED units. This study highlights predictive factors of mortality that will help clinicians in recognizing and managing patients at risk of death.